Physics Learning Based on Practicum: Factors that Affecting Expansion - Eduarsyah, Eduarsyah; ., Devi Astriani (Journal of Education and Vocational Research, 2015)
An object when heated will undergo expansion. Expansion of an object is affected by the expansion coefficient, temperature, and type of object substances that cause the length, area, and volume of the object and other objects differently. Based on these concepts, to investigate the comparative increase in the size of the object that is affected by factors that affect the expansion by heating the body until it reaches the equilibrium temperature. As the object under study will use a block of copper and water with each volume to be measured 10-5 m3 added volume ratio. With the initial temperature of each object 20 oC, both substances will be heated up to a temperature of 30oC, 35oC, 40oC, 45oC, dan 50oC. Both substances are then calculated and compared to the increase in volume experimentally and theoretically. After calculation, a score which indicates that the copper block and the water volume is different. Increase the volume of water is greater than the increase in the volume of copper block in each temperature increment. Both these substances are two different substances that have different volume expansion coefficient as well. So we get that expansion coefficient, temperature, and type of object substances have an affect on the expansion that occurs on an object.